Research on the Risk Assessment of Water Inrush From the Roof of the Fully Mechanized Mining Face in Huanglong Jurassic Coalfield - Yanbo Hu; Wenbo Feng; Gang Zheng; Xinmin Chen (Geofluids)
The frequent occurrence of water inrush disasters from the fissured aquifer of the Lower Cretaceous Luohe Formation sandstone in the Jurassic coalfield of Huanglong, due to mining-induced disturbances in the roof, poses a significant threat to the safe production of mines. To ensure mine safety, this study investigates key indicators such as water source recharge, water-conducting pathways, and recharge intensity. A mathematical model based on multiple disaster-causing factors was developed, and a water hazard evaluation system for the Jurassic coalfield in the Huanglong region was established using a GIS platform. Validation through underground borehole data revealed a high correlation between the evaluation results and the verification data, with boreholes in stable zones showing low inflow rates (< 5 m3/h), while anomalous and hazardous zones demonstrated higher inflow, confirming the effectiveness and accuracy of the assessment system. The findings of this study provide a scientific basis for water hazard prevention and control during coal seam mining in the Huanglong Jurassic coalfield and surrounding areas.